2003
DOI: 10.1177/0887302x0302100303
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Micro Apparel Enterprises in Botswana: Motivations, Practices, Challenges, and Success

Abstract: The purpose of this research was to develop a profile of micro apparel enterprises in Botswana and to examine the profile for cross-cultural applicability in relation to small business scholarship. Field interviews with 24 businesswomen revealed that the women employed an average of three workers and had operated their firms for three to five years. The profile identified motivations for initiating a business; business practices related to employees, product development, and marketing; challenges faced as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Research studies have elaborated some of the barriers faced by female entrepreneurs in setting up their businesses. A study done by Gobagoba and Littrell (2003) found that female entrepreneurs faced a variety of barriers: lack of management skills, business skills, cash flow, technical skills and the ability to recruit qualified staff. In addition, the authors found that women entrepreneurs have limited access to appropriate technology.…”
Section: Barriersmentioning
confidence: 99%
“…Research studies have elaborated some of the barriers faced by female entrepreneurs in setting up their businesses. A study done by Gobagoba and Littrell (2003) found that female entrepreneurs faced a variety of barriers: lack of management skills, business skills, cash flow, technical skills and the ability to recruit qualified staff. In addition, the authors found that women entrepreneurs have limited access to appropriate technology.…”
Section: Barriersmentioning
confidence: 99%
“…Research so far has elaborated some of the barriers faced by women entrepreneurs in setting up their businesses. A study done by Gobagoba and Littrell (2003) found that women entrepreneurs faced a variety of barriers: lack of management skills, business skills, cash flow, technical skills, and the ability to recruit qualified staff. In addition, the authors found that they have limited access to appropriate technology and have difficulty in networking.…”
Section: Barriers Faced By Women Entrepreneursmentioning
confidence: 99%
“…Commercial banks were reluctant to lend money to small scale business as they lacked business skills, had high cost risk and that small business emphasized on short term survival issues while banks were for long-term competitiveness (Gwebu, 2005;Pansiri and Temtime 2005). Botswana government and the private sector have been assisting micro enterprises but not paying much attention on the component of training small business owners on how to manage their businesses for long term survival in the market (Gobagoba and Littrell, 2003;BIDPA and CEDA, 2007. In developing countries urban planners formulate policies to control the operation of the informal sector activities particularly street vending (Palmer, 2007) but some of these policies are not friendly to street vendors (Palmer, 2007;Joseph, 2011). For instance, they carry out frequent inspection and do demolitions, confiscation of goods and sometimes remove some street vendors from where they operate (Joseph, 2011).…”
Section: Importance Of Street Vendors In Botswanamentioning
confidence: 99%
“…Although Botswana does not have a comprehensive informal sector development policy, Botswana realized the potential and importance of Small, Medium and Micro enterprises (SMMEs) in creating jobs and generating income (Narayan et al, 2004). Taking into account the socio-economic objectives incorporated in the National Development Plans, Botswana's SMMEs policy, first of its kind was approved in 1998 as an integral part of the government's strategy for industrial development and economic diversification with the intention of developing informal sector (Gobagoba and Littrell, 2003;Narayan et al, 2004;Kuruba, 2010). This policy is the result of the recommendations of the SMME Task force appointed by the then Minister of Commerce and Industry (Kuruba, 2010).…”
Section: Strategies To Resolve Challenges Faced By Street Vendorsmentioning
confidence: 99%
See 1 more Smart Citation